2017
DOI: 10.1128/jvi.02428-16
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Benchmark Profile for HIV-1 Envelope Glycoprotein Production Based on Eleven Env Trimers

Abstract: HIV-1 envelope glycoprotein (Env) glycosylation is important because individual glycans are components of multiple broadly neutralizing antibody epitopes, while shielding other sites that might otherwise be immunogenic. The glycosylation on Env is influenced by a variety of factors, including the genotype of the protein, the cell line used for its expression, and the details of the construct design. Here, we used a mass spectrometry (MS)-based approach to map the complete glycosylation profile at every site in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 70 publications
6
112
3
Order By: Relevance
“…Hence, there are no indications that SOSIP trimer expression in CHO cells is problematic from the antigenicity perspective. This assessment is consistent with reports that producer cell variation has only a subtle influence on the glycosylation of native-like trimers (48)(49)(50).…”
Section: Resultssupporting
confidence: 92%
“…Hence, there are no indications that SOSIP trimer expression in CHO cells is problematic from the antigenicity perspective. This assessment is consistent with reports that producer cell variation has only a subtle influence on the glycosylation of native-like trimers (48)(49)(50).…”
Section: Resultssupporting
confidence: 92%
“…Purification can also be problematic. These translational difficulties reflect the extensive glycosylation of HIVā€1 Env, with glycans comprising half the mass, and also the presence of nine intramolecular disulfide bonds in the gp120 subunit and another in gp41 (Behrens & Crispin, ; Go et al, ; Ward & Wilson, ). The processing state of the glycans has proven to be particularly sensitive to the precise quaternary structure of the Env complex (Behrens & Crispin, ; Pritchard et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(ii) To identify the variables that impact Env's glycosylation profile at sites with divergent glycosylation. The study concluded that the processing of many glycosylation sites on recombinant Envs are not affected by the expression system …”
Section: Role Of Mass Spectrometry In the Vaccine Developmentmentioning
confidence: 99%